The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/anie.201608009
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Tetrazine Derivatives for Rapid Bioorthogonal Decaging in Living Cells

Abstract: The inverse-electron-demand Diels-Alder (iDA) reaction has recently been repurposed as a bioorthogonal decaging reaction by accelerating the elimination process after an initial cycloaddition between trans-cyclooctene (TCO) and tetrazine (TZ). Herein, we systematically surveyed 3,6-substituted TZ derivatives by using a fluorogenic TCO-coumarin reporter followed by LC-MS analysis, which revealed that the initial iDA cycloaddition step was greatly accelerated by electron-withdrawing groups (EWGs) while the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 57 publications
5
137
0
1
Order By: Relevance
“…Consequently, electron withdrawing substitution on 3- and 6- position of the tetrazine lowered the LUMO of the diene and therefore accelerate the reaction [20, 21]. Recently, the iEDDA reaction has been redirected as an attractive bioorthogonal decaging reaction [2527]. Interestingly, both electron donating group (EDG) and electron withdrawing group (EWG) decreased the decaging process.…”
Section: Tetrazine and [4 + 2] Cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, electron withdrawing substitution on 3- and 6- position of the tetrazine lowered the LUMO of the diene and therefore accelerate the reaction [20, 21]. Recently, the iEDDA reaction has been redirected as an attractive bioorthogonal decaging reaction [2527]. Interestingly, both electron donating group (EDG) and electron withdrawing group (EWG) decreased the decaging process.…”
Section: Tetrazine and [4 + 2] Cycloadditionmentioning
confidence: 99%
“…Interestingly, both electron donating group (EDG) and electron withdrawing group (EWG) decreased the decaging process. For example, Peng Chen group systematically studied the kinetic effect of substituents on tetrazine for decaging reaction [27]. They synthesized symmetric tetrazine having the same substituents on 3- and 6- position of tetrazine.…”
Section: Tetrazine and [4 + 2] Cycloadditionmentioning
confidence: 99%
“…For preparation of tetrazine surfaces ( M 4 ), we chose unsymmetrical tetrazine with benzyl amine and methyl substitution, again via a carbamate linkage to ensure the same freedom/buried nature as in M 2 / M 3 . As shown by the groups of Hilderbrand and Chen, unsymmetrical tetrazines provide a better balance between stability and reactivity than their symmetric counterparts, while also ensuring enough rigidity on a surface. Complete surface attachment for M 4 surfaces was obtained for this reaction as confirmed by N/P ratios (1.5±0.1) in XPS analysis (Figure S5.4 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Several strategies were pursued to achieve simultaneously high release yields and accelerated reactions. Investigations into tetrazines revealed that those with combinations of electron‐poor aryl substituents and linear alkyl substituents provide high elimination yields and rapid reaction rates . 2‐(6‐(Pyrimidin‐2‐yl)‐1,2,4,5‐tetrazin‐3‐yl)ethan‐1‐ol ( 3 ; Scheme ) allowed over 80 % uncaging in 30 min, whereas 1 only provided 20 % uncaging at this point in time.…”
Section: Reported Dissociative Bioorthogonal Reactionsmentioning
confidence: 99%